2010
DOI: 10.1021/ac100771r
|View full text |Cite
|
Sign up to set email alerts
|

Overflow Microfluidic Networks for Open and Closed Cell Cultures on Chip

Abstract: Microfluidics have a huge potential in biomedical research, in particular for studying interactions among cell populations that are involved in complex diseases. Here, we present "overflow" microfluidic networks (oMFNs) for depositing, culturing, and studying cell populations, which are plated in a few microliters of cell suspensions in one or several open cell chambers inside the chip and subsequently cultured for several days in vitro (DIV). After the cells have developed their phenotype, the oMFN is closed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…This platform provides a model system to study and dissect the specific intercellular pathways involved in a variety of processes and neural disease states. 51 Fabrication of guiding 3D structures for neural engineering has also employed compartmentalization and harnessed 3D microfluidic devices to construct neural layers and 3D architecture. Kunze et al, demonstrated agarose-alginate mixtures that form multilayered scaffolds with embedded primary cortical neuron layers separated from each other by cell-free layers.…”
Section: Neuralmentioning
confidence: 99%
“…This platform provides a model system to study and dissect the specific intercellular pathways involved in a variety of processes and neural disease states. 51 Fabrication of guiding 3D structures for neural engineering has also employed compartmentalization and harnessed 3D microfluidic devices to construct neural layers and 3D architecture. Kunze et al, demonstrated agarose-alginate mixtures that form multilayered scaffolds with embedded primary cortical neuron layers separated from each other by cell-free layers.…”
Section: Neuralmentioning
confidence: 99%
“…Many designs seek to create a userfriendly experience for the researcher and a more benign microenvironment for the cells. 22,[32][33][34] In open-chamber designs, in which cells are bathed in the bulk media bath like in a petri dish, results can be directly compared with conventional cell cultures. Open-chamber microfluidic devices circumvent the media-replenishing problem of closed devices by operating within an open reservoir, allowing for easy media exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic platforms that allow for precise control over cell seeding, cell culture, and the chemical microenvironment of cells have been developed to study intercellular communication. [13][14][15][16][17][18] Many of these studies are restricted to two-dimensional (2D) cell cultures, whereas 3D cell cultures are known to be more physiologically relevant. [19][20][21][22] Microfluidic platforms have also been developed to pattern cells in 3D constructs using laminar flow.…”
mentioning
confidence: 99%